Analisis Tingkat Partisipasi Masyarakat dalam Pengembangan Wisata Bukit Telaga dan Goa (Bulaga) di Desa Pucakwangi Kecamatan Babat Kabupaten Lamongan - FIRRIZQI, Mutiara; Wahyudi, Kalvin Edo (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
The many tourist attractions in Indonesia have the potential to continue to be developed, one of which is Bukit Telaga and Goa Tourism (BULAGA). Tourism development requires active community involvement. Community participation in development can run well if the community is directly involved in the activity process. However, in the development of Bulaga Tourism, there are still several problems that occur such as the lack of tourism promotion and limited funds to carry out comprehensive development. This study aims to describe community participation in the development of hills, lake and cave (BULAGA) in Pucakwangi Village, Babat District, Lamongan Regency. The type of research used is descriptive qualitative. Data collection was carried out through interviews, observations, and documentation using purposive sampling techniques. The results of the study showed that community participation in the development of Bulaga Tourism was quite good. Community participation is indicated to be at the level of providing support to develop Bulaga Tourism. However, even though it is at the highest level, in its development Bulaga Tourism still requires collaboration with various parties and effective promotion in order to become sustainable tourism.